Analisis Hybrid Contract Pada Sukuk Tabungan Seri ST012 Perspektif Fikih Muamalah - Syibromalisi, Fatwa (Sharia Faculty Islamic Economic Law Study Department, 2024)
AbstractSukuk savings series ST012 is an SBSN issued using a Hybrid Contract in the form of wakalah, ijarah, bai', and wa'd contracts. The Hybrid Contract has been widely studied by Fuqaha which is generally referred to as al-'Uqud al-Murakkabah. However, some scholars prohibit implementing hybrid contracts based on the hadith of the prophet such as the concept of shafqataini fi shafqatin, bai' wa salaf, and bai'ataini fi bai'atin. So this study aims to examine the law of issuing sukuk savings series ST012 from the perspective of muamalah fiqh. This study uses a literature study method, with a normative approach sourced from books, journals, laws, DSN-MUI Fatwas, and other sources relevant to the research object. The results of the research show that the ST012 series savings sukuk are included in al-'Uqud al-Murakkabah, the contracts of which cannot be separated or are interrelated (al-'Uqud al-Mutaqabilah). In practice, ST012 is by Sharia provisions because the contracts are not contradictory (mutanaqidhah). This means that there is no element of gharar, mutual pleasure, and benefits the parties.Keywords: Sukuk Savings, Hybrid Contract, ST012. AbstrakSukuk tabungan seri ST012 merupakan SBSN yang diterbitkan menggunakan Hybrid Contract yaitu berupa akad wakalah, ijarah, bai’, dan wa’d. Adapun Hybrid Contract telah banyak dikaji oleh para Fuqaha yang umumnya disebut dengan istilah al-‘Uqud al-Murakkabah. Akan tetapi Sebagian ulama melarang pelaksanaan hybrid contract berdasarkan hadis nabi seperti pada konsep shafqataini fi shafqatin, bai’ wa salaf, dan bai’ataini fi bai’atin. Sehingga penelitian ini bertujuan untuk mengkaji hukum penerbitan sukuk tabungan seri ST012 perspektif fikih muamalah. Penelitian ini menggunakan metode studi kepustakaan, dengan pendekatan normatif yang bersumber dari buku, jurnal, undang-undang, Fatwa DSN-MUI dan sumber lain yang relevan dengan objek penelitian. Hasil dari penelitian menunjukan bahwa sukuk tabungan seri ST012 termasuk dalam al-‘Uqud al-Murakkabah yang di antara akad-akadnya tidak dapat dipisahkan atau saling berkaitan (al-‘Uqud al-Mutaqabilah). ST012 dalam praktiknya telah sesuai dengan ketentuan syariah karena akad-akadnya tidak berlawanan (mutanaqidhah). Maknanya tidak terdapat unsur gharar, saling rida, dan menguntungkan para pihak.Kata Kunci: Sukuk Tabungan, Hybrid Contract, ST012. Abstract Sukuk savings series ST012 is an SBSN issued using a Hybrid Contract in the form of wakalah, ijarah, bai', and wa'd contracts. The Hybrid Contract has been widely studied by Fuqaha which is generally referred to as al-'Uqud al-Murakkabah. However, some scholars prohibit implementing hybrid contracts based on the hadith of the prophet such as the concept of shafqataini fi shafqatin, bai' wa salaf, and bai'ataini fi bai'atin. So this study aims to examine the law of issuing sukuk savings series ST012 from the perspective of muamalah fiqh. This study uses a literature study method, with a normative approach sourced from books, journals, laws, DSN-MUI Fatwas, and other sources relevant to the research object. The results of the research show that the ST012 series savings sukuk are included in al-'Uqud al-Murakkabah, the contracts of which cannot be separated or are interrelated (al-'Uqud al-Mutaqabilah). In practice, ST012 is by Sharia provisions because the contracts are not contradictory (mutanaqidhah). This means that there is no element of gharar, mutual pleasure, and benefits the parties.Keywords: Sukuk Savings, Hybrid Contract, ST012. AbstrakSukuk tabungan seri ST012 merupakan SBSN yang diterbitkan menggunakan Hybrid Contract yaitu berupa akad wakalah, ijarah, bai’, dan wa’d. Adapun Hybrid Contract telah banyak dikaji oleh para Fuqaha yang umumnya disebut dengan istilah al-‘Uqud al-Murakkabah. Akan tetapi Sebagian ulama melarang pelaksanaan hybrid contract berdasarkan hadis nabi seperti pada konsep shafqataini fi shafqatin, bai’ wa salaf, dan bai’ataini fi bai’atin. Sehingga penelitian ini bertujuan untuk mengkaji hukum penerbitan sukuk tabungan seri ST012 perspektif fikih muamalah. Penelitian ini menggunakan metode studi kepustakaan, dengan pendekatan normatif yang bersumber dari buku, jurnal, undang-undang, Fatwa DSN-MUI dan sumber lain yang relevan dengan objek penelitian. Hasil dari penelitian menunjukan bahwa sukuk tabungan seri ST012 termasuk dalam al-‘Uqud al-Murakkabah yang di antara akad-akadnya tidak dapat dipisahkan atau saling berkaitan (al-‘Uqud al-Mutaqabilah). ST012 dalam praktiknya telah sesuai dengan ketentuan syariah karena akad-akadnya tidak berlawanan (mutanaqidhah). Maknanya tidak terdapat unsur gharar, saling rida, dan menguntungkan para pihak.Kata Kunci: Sukuk Tabungan, Hybrid Contract, ST012.